(3GdeajO aj TQM YeOI GdeLjO aj GdfXe hGdJLhjOs - (3ESeGYjd Hf eMeO Hf ESeGYjd GdabGYj Hf SYOGddg GdeYQha HGHf GdabGYj GdMehjs; (3Yde GdOjf Ydj Hf eMeO GdSNGhj,J (B643 (3g` s
(3ChdgG (B:s
(3hHYO hdeG cGfJ fhfjI GdEeGe CHhGdMSf GdSNGhj GdeSeGI YeOI GdeLjO aj GdfXe hGdJLhjO s
(3BNQgG (B:s
(3ef GdcdGe Ydi gPg GdbUjOI Ydi SHjd GdGNJUGQ Cfg CQMe GdQGMejf s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B332s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1172s
Keywords: (3GdbQGAGJ hGdJLhjOs